Chemical cleaning of biologically fouled membranes - Huang, Yingwen. (2013)
Microorganisms tend to attach to a solid surface in natural and engineered environment and can further grow into a gel layer known as biofilm, which is the main cause of membrane biofouling. This study investigated the chemical treatment of biologically fouled membranes. Biofilm was grown on nylon membranes to stimulate biofoul conditions, which was then treated by 6 different types of chemicals, namely sodium hydroxide, sodium hypochlorite, sodium chloride, Ethylenediaminetetraacetic acid (EDTA), citric acid and hydrogen peroxide. The effects of chemical concentrations were also studied in the range of 0.5-5%. The removal efficiency of biofims by 6 chemicals was determined in terms of fixed biomass, extracellular proteins (PN) and extracellular polysaccharides (PS).